RITUAL â€œKLIWONANâ€ BAGI MASYARAKAT BATANG - Widyatwati, Ken (Faculty of Humanities, Diponegoro University, 2014)
The narrative have a meaning and structure. The structure of kliwonanÂ myth is representation form the society, who to support. Structure or model to become representation from the society to exist in stage unconscious, and only to be looking for with structuralism Levi-Straus Analysis. KliwonanÂ RitualÂ for Batang Society is a folklore wich BatangÂ society.Â Kliwonan RitualÂ Â is not ritual content, but it have many contents be trusted by community, The aim of this research is description ofÂ kliwonanÂ Ritual for Batang Society areÂ component Identification, and the content of myth. This Ritual perform every Jumat Kliwon dayÂ in Javanese Callender. Time isÂ 14.00-18.00 am. The place is Alun-alun Batang, Central Java. The content ofÂ Exorcism RitualÂ for Batang Society is place, time, instrument, ritual offering, prayer and myth. This myth is jumat kliwonÂ and kliwonanÂ Â Ritual..